Aya Sofia Constantinople as recently restored by order of H. M. The Svltan Abdvl Medjid from the original drawings by Chevalier Caspard Fossati litographed by Lovis Haghe esq. (İstanbul)
[13] sayfa, [25] yaprak gravür